INVESTIGATION OF TECTONOMAGNETIC EFFECTS IN ARARAT SEISMIC POLYGON AIMING TO STUDY MODERN MOVEMENTS OF EARTH CRUST (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The results of the tectonomagnetic studies of 5 profiles in the Ararat Seismic Polygon during 2013–2014 are given in the work. To allocate tectonomagnetic effects it is planned to carry out measuring twice a year, which will allow to reveal the local geomagnetic variations conditioned by the tectonic processes.
Keywords: tectonomagnetic effect; secular trend; modern movements of Earth crust; Ararat seismic polygon